Flexibilidade e eficiência na cognição social - Daniel de Lucas Silveira de Noronha (2013)
The main objectives of this dissertation are (i) to explore the concepts of flexibility and efficiency in the domain of social cognition and (ii) to argue that these concepts are in a complementary relationship. A central motivation for this is the fact that the contemporary debate in this domain, that opposes mentalists and interactionists, leads us to a position where we have to choose between two implausible alternatives: either emphasizing flexibility at the expense of efficiency (the mentalist side), or focusing on efficiency at the expense of flexibility (the interactionist side). However, flexibility and efficiency are both critical desiderata of the explanation of social cognition. With regard to flexibility, agents are responsive to the fact that different mental states can explain/cause one and the same behavior, and, inversely, different corporal movements can be explained/caused by one and the same mental state. According to mentalist theories, this flexibility is based on a folk theory of mind (theory-theory), or based on the interpreter's own cognitive resources (theory of simulation). However, the problem is that these theories are committed to a very cognitively demanding notion of flexibility. As a matter of fact, mutual comprehension is not only flexible, but also efficient. Contrary to the mentalist paradigm, recent theories of social cognition based on the extended cognition paradigm, such as the interactionist theory, aim to provide an image of social cognition that meets the efficiency demands. The strategy is to argue that in ordinary situations of interaction, what is available to the mutual perception of agents are behaviors endowed with mentality. Therefore, typically, agents do not need to appeal to extra-perceptual mechanisms in order to understand each other. The problem here, however, is that the emphasis on the efficiency can lose sight of flexibility. It fails to accommodate the comprehension of mental states that are far from the action, such as false beliefs. In order to take into account this comprehension, one should consider some level of flexibility. The situation before us is, then, the following one: without the pressures coming from flexibility, there are rigid expectations of behavior based on causal regularities. On the other hand, without the pressures coming from efficiency, there is a complicated notion of flexibility, one that does not fit with what is required in co-presence episodes. In view of this, the dissertation advances an alternative that takes into account the dynamic relationship between flexibility and efficiency. It argues that the capabilities that characterize flexibility are partially dependent on our engagement in ordinary situations of interaction, and, on the other hand, argues that the capabilities that characterize efficiency, which generate the fluent aspect of interactions, would not be stable without the relationship with inferential capabilities.